Intuitive Ethnomathematics: A Case Study of Lopi Sandeq's Construction Non Formal Math Calculations - Suharto, Nuraimah; Suradi; Bernard (Cita konsultindo, 2025)
Ethnomathematics plays a crucial role in exploring Indonesia's rich cultural diversity, particularly concerning the Lopi Sandeq, a traditional boat of the Mandar Tribe in West Sulawesi. This research investigates the intuitive ethnomathematics employed in the construction of the Lopi Sandeq, a process that traditionally eschews formal mathematical calculations. The study aims to delve into how intuition, honed through generations of experience and acute visual perception, serves as the primary determinant for achieving the boat's renowned balance and precision. Utilizing a qualitative approach with an interpretive phenomenological design, the research gathered data through in-depth interviews, participatory observation, and documentation from experienced Lopi Sandeq boat builders (passandeq) in West Sulawesi. The findings reveal that while basic measurements may be used as initial references, critical decisions regarding the boat's balance and symmetry are predominantly based on subjective, adaptive assessments, deeply internalized feelings, and visions developed over decades. This intuitive approach, which incorporates concepts like symmetry, proportion, and basic measurements, demonstrates that technical precision can be achieved through non-formal knowledge pathways. The study highlights that the construction of Lopi Sandeq reflects a unique integration of cultural values, such as the symbolic use of odd numbers and shapes resembling Arabic letters, and practical, empirically derived knowledge. This research enriches ethnomathematical perspectives by demonstrating diverse ways humans apply spatial and equilibrium principles within cultural contexts, underscoring the validity and effectiveness of non-formal knowledge. The intuitive wisdom embedded in Lopi Sandeq construction serves as tangible evidence of a rich cultural heritage, offering valuable lessons in adaptation, innovation, and human-environment harmony. It also provides a robust case study for teaching mathematical concepts in a meaningful and culturally relevant way